Politics, partisanship and the power to veto: does gubernatorial line-item veto power affect state budgets?. Issue 33 (15th July 2018) - McCormack, Joseph; Reingewertz, Yaniv
ABSTRACT: How does line-item veto (LIV) power affect a governor's ability to structure the state budget? Is LIV power only relevant as a partisan tool? Is it still relevant when the state legislature can override the veto? We use a rich disaggregated data set to test the effect of the gubernatorial LIV on state budgets, controlling for political factors such as party affiliation of the governor and legislature, minority status of the governor, and the legislature's ability to override a LIV. Our results suggest that LIV power has very weak influence, if any, on governors' ability to influence state budgets.